THE COSMOLOGICAL ARCHITECTURE OF BEURACAN MOSQUE AS THE REPRESENTATIVE CULTURAL ACCULTURATION IN ACEH - Mira Alfitri; Putri Maurissa (Arsitekno, 2026)
Architectural cosmology refers to a conceptual understanding of the universe rooted in cultural beliefs and expressed through spatial organization, orientation, and symbolic elements in architecture. The Beuracan Mosque, located in Pidie Jaya Regency, Aceh Province, serves as the object of this study, demonstrating cosmological values embedded in its spatial arrangement, and symbolic features as a manifestation of cultural acculturation in Aceh. This research employs a qualitative-descriptive methods, with primary data and secondary data. The study focuses on the cosmological aspects of architecture, spatial organization, orientation, and symbolic elements that convey cosmological meanings shaped by the acculturation of Hindu, Buddhist, and Islamic cultures. The findings reveal that the mosque embodies cosmological values through the representation of the universe’s structure in both horizontal and vertical spatial arrangements, as well as in its orientation and simbols. The process of Islamization of Hindu and Buddhist elements in the Mosque occurs in an integrative manner, resulting in a unique and contextual sense of sacredness. The mosque can be regarded as a representative example of cosmological architecture shaped by cultural acculturation in Aceh, contributing to the broader discourse on Islamic architecture in the region and the Indonesian archipelago.